Sleep impact on obesity – literature review - Buczek, Kacper; Kulig, Klaudia; Wiśniowski, Maksymilian; Stanibuła, Dominik; Zwierzchlewska, Patrycja; Redner, Aneta; Rybowski, Jakub; Popiel, Michal; Głowacz, Julia; Dziekoński, Kamil (Quality in Sport, 2025)
Purpose: The aim of this literature review is to analyze existing studies on the relationship between sleep and obesity, with a focus on how sleep quality, duration, and circadian rhythm disruptions influence obesity development. It also identifies biological mechanisms, such as changes in appetite-regulating hormones, and evaluates the effectiveness of sleep-related interventions in obesity prevention and treatment. Methodology: A systematic review of scientific literature was conducted, including clinical trials, cohort studies, and meta-analyses from the last 10 years. The review examined various populations and age groups, focusing on the impact of sleep duration, quality, and circadian rhythm disturbances on obesity. Findings: Results consistently show that poor sleep quality and short sleep duration (<6 hours) are associated with higher BMI, increased waist circumference, and visceral fat. Sleep disturbances impact hormones like ghrelin and leptin, promoting overeating. Circadian disruptions from shift work or social jetlag further contribute to abdominal fat. Sleep improvement interventions have shown promising effects on weight reduction, though long-term impact requires more study. Conclusions: This review highlights the important role of sleep in obesity development. Poor sleep duration and quality, along with circadian misalignment, are linked to weight gain and metabolic dysfunction. While sleep-targeted interventions show potential for improving metabolic health and aiding weight loss, further research is needed to fully understand underlying mechanisms and lasting effects. Integrating sleep management into obesity prevention and treatment could offer a valuable strategy to address the global obesity epidemic.